Groundwater, Soil, and Vegetation Interactions at Discrete Riparian Inflow Points (DRIPs) and Implications for Boreal Streams - Ploum, Stefan W.; Leach, Jason A.; Laudon, Hjalmar; Kuglerová, Lenka (Frontiers in Water, 2021)
Hydrological processes at hillslope and catchment scales explain a large part of stream chemistry dynamics through source-transport mechanisms from terrestrial to aquatic ecosystems. Riparian zones play a central role, as they exert a strong influence on the chemical signature of groundwater discharge to streams. Especially important are riparian areas where upslope subsurface flow paths converge, because they connect a large part of the catchment to a narrow section of the stream. Recent research shows that both in terrestrial and aquatic ecosystems, riparian convergence zones fulfill important biogeochemical functions that differ from surrounding riparian zones. Most catchment-scale conceptual frameworks focus on generalized hillslope-riparian-stream transects and do not explicitly consider riparian convergence zones. This study integrates collective work on hydrology, groundwater chemistry, vegetation and soils of discrete riparian inflow points (DRIPs) in a boreal landscape. We show that compared to adjacent riparian forests, DRIPs have groundwater levels that are consistently near the surface, and supply organic-rich water to streams. We suggest that interactions between hydrology, wetland vegetation, and peat soil development that occur in DRIPs leads to their unique groundwater chemistry and runoff dynamics. Stream-based studies show that across flow conditions, groundwater inputs from DRIPs to headwater reaches influence stream temperature, water chemistry and biology. As such, accounting for DRIPs can complement existing hillslope and stream observations, which would allow better representation of chemical and biological interactions associated with convergence of subsurface flow paths in riparian zones.